Camarillo Airport Authority/Oxnard Airport Authority Minutes - Rodney L. Murphy:::::: (1998)
The minutes and agenda of a joint meeting between the Camarillo Airport Authority and the Oxnard Airport Authroity. Discusses the Airport Noise Abatement Program and Policies as well as a review of County Airport Land Use Commission membership.